Purification, characterization, and antiproliferative activity of L-methioninase from a new isolate of Bacillus haynesii JUB2 - Brinda Bojamma Kotramada Bopaiah, Diana Aiyandra Nanda Kumar, Kohini Balan, Lucky Dehingia, Manoj Kumar Ramanayakanahalli Venkatesh Reddy, Ashrini Bhaktavalsala Suresh, Varalakshmi Kilingar Nadumane (Journal of Applied Pharmaceutical Science, 2020)
L-methioninase (MGL) has received much attention in the recent years, since it shows antiproliferative activity and methionine restriction has been known to arrest tumor growth. Methionine dependence is the only known general metabolic defect in cancers. Normal cells have the ability to grow on homocysteine, instead of methionine, due to their active methionine synthase. Thus, depleting cellular/plasma methionine levels using MGL seems to be a promising therapeutic approach to treat cancer. Therefore, the objective of the present study is isolation of soil microbes using the selective M9 media for MGL producers and screening them for MGL activity. The results showed a novel bacterial strain, identified as Bacillus haynesii JUB2, which exhibited highest specific activity of 9.22 U/mg of protein. This enzyme was purified by acetone precipitation and diethylaminoethyl column methods. Upon column purification, fraction 6 yielded the highest enzyme activity and the specific activity increased enormously to 102.15 U/mg of protein. The cytotoxicity 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium bromide assay performed on breast (MCF-7) and liver cancer cell lines (HepG2) showed highest cytotoxicity with a percentage viability of 63.2 and 68.6, respectively, at 250 μg/ml concentration. It can be concluded that purified MGL from the new source of B. haynesii JUB2 holds promise toward anticancer studies.
Keywords: Anticancer, Bacillus haynesii, cytotoxic, ion-exchange chromatography, L-methioninase.